Pilot cohort study of obstructive sleep apnoea in community-dwelling people with schizophrenia. (24th March 2021) - Myles, H.; Myles, N.; Vincent, A. D.; Wittert, G.; Adams, R.; Chandratilleke, M.; Liu, D.; Mercer, J.; Vakulin, A.; Chai-Coetzer, C. L.; Galletly, C.
Abstract : Objectives: We aimed to assess the incidence of obstructive sleep apnoea (OSA) in people with schizophrenia, to explore clinical associates with OSA and how well OSA screening tools perform in this population. Methods: All patients registered in a community outpatient Clozapine clinic, between January 2014 and March 2016, were consecutively approached to participate. Participants were screened for OSA using at home multichannel polysomnography (PSG) and were diagnosed with OSA if the apnoea-hypopnoea index (AHI) was >10 events/hr. Univariate comparison of participants to determine whether AHI > 10 events/hr was associated with demographic factors, anthropometric measures and psychiatric symptoms and cognition was performed. The sensitivity, specificity, positive predictive value and negative predictive value of the commonly used sleep symptoms scales and OSA screening tools were also determined. Results: Thirty participants were recruited, 24 men and 6 women. Mean age was 38.8 (range: 25–60), and mean body mass index (BMI) was 35.7 (range 19.9–62.1). The proportion of participants with OSA (AHI > 10 events/hr) was 40%, 18 (60%) had no OSA, 4 (13%) had mild OSA (AHI 10.1–20), zero participants had moderate OSA (AHI 20.1–30) and 8 (27%) had severe OSA (AHI > 30). Diagnosis of OSA was significantly associated with increased weight, BMI, neck circumference and systolic blood pressure. Diagnosis of OSA was not significantly associated with Positive and Negative Symptoms Scale, Montgomery Asperger's Depression Rating Scale, Personal and Social Performance scale or Brief Assessment of Cognition for Schizophrenia scores. All OSA screening tools demonstrated poor sensitivity and specificity for a diagnosis of OSA. Conclusion: OSA was highly prevalent in this cohort of people with schizophrenia and was associated with traditional anthropometric OSA risk factors.